Early fluid resuscitation in the management of major burns: Ten years experience in Tabuk, Saudi Arabia - Rahoma, A.H. (Faculty of Medicine, University of Malaya, 2002)
During the period from January 1992 up to the end of July 2001, the Burns Unit in King Khalid'C'Hospital treated 1735 cases of burns. The burns cases were of varying causes, age groups, degree, depth and extent. The formula used in Teating these burns patients was a modification of Parkland fonnula. The fluid used was Ringer lactate solution. This fluid was administered for the first 3 days post burn until the general condilion of the palient was sfabilized. Early oral intake was encouraged in aU patients and was started as early as the second or the third day. Colloids were given by the end of the third or even the fourth day and according to the individual patients' needs. The results of this treatment regime significantly avoided renal complications and ensured patient rehydration.